Consent Codes: Upholding Standard Data Use Conditions. - Stephanie O M Dyke; Anthony A Philippakis; Jordi Rambla De Argila; Dina N Paltoo; Erin S Luetkemeier; Bartha M Knoppers; Anthony J Brookes; J Dylan Spalding; Mark Thompson; Marco Roos; Kym M Boycott; Michael Brudno; et al. (PLoS Genetics)
A systematic way of recording data use conditions that are based on consent permissions as found in the datasets of the main public genome archives (NCBI dbGaP and EMBL-EBI/CRG EGA).